BASIC SOCIO-CULTURAL SCIENCE: ASPECTS OF HUMAN BEHAVIOR AS INDIVIDUAL AND SOCIAL BEINGS IN THE SPHERE OF COMMUNITY LIFE IN BIG CITIES - Maruf Nasution, Fahri; Maydina Nasution, Rafikah (International Journal of Students Education, 2023)
Public space is a part of the city which is very important in city life. As a public open space, the community can carry out many activities both individually and in groups. The characteristics of a person as an individual and as a social being, it is interesting to study how humans maintain their privacy in public spaces that are open to all. Therefore, the purpose of this study is to provide an overview of how humans manifest their nature as individual beings in social space in public spaces, so that the benefits of this research are that urban planners are expected to be able to use the urban planner's attention to community needs. nature as a user of this room. A qualitative literature review approach is used as a research method, ie. based on a literature review based on various relevant theories and research articles, it was concluded that human nature as an individual being and as a social being are two forms in the public space, namely personal. outer space ) is a virtual space that surrounds the body and territory of each individual, formed according to certain conditions but can still be disturbed by other individuals, so that the human defense is not massive. Territory is also influenced by two factors, namely the economy and culture. formed according to certain conditions but can still be disturbed by other individuals, so that the human defense is not massive. Territory is also influenced by two factors, namely the economy and culture. formed according to certain conditions but can still be disturbed by other individuals, so that the human defense is not massive. Territory is also influenced by two factors, namely the economy and culture.